Investigation of Ventilation Energy Recovery with Polymer Membrane Material-Based Counter-Flow Energy Exchanger for Nearly Zero-Energy Buildings - Miklos Kassai; Laith Al-Hyari (Energies, 2019)
The usage of energy recovery ventilation units was extended in European countries. Air-to-air heat and energy recovery is an effective procedure to reduce energy consumption of the ventilation air. However, the material of the core significantly influences the performance of the exchangers, which is becoming an extremely important aspect to meet the energy requirements of nearly zero-energy buildings. In this study, the performance of two counter-flow heat/enthalpy energy exchangers are experimentally tested under different operating conditions, and the values of the sensible, latent, and total effectiveness are presented. Moreover, the effects of the material of two exchangers (polystyrene for the sensible heat exchanger and polymer membrane for the energy exchanger) on the energy consumption of ventilation in European cities with three different climates (in Reykjavík in Iceland as a cold climate, in Budapest in Hungary as a temperate climate, and in Rome in Italy as a warm climate) are evaluated. The results show that the energy recovery of ventilation air with a polymer membrane material-based counter-flow energy exchanger performs better than using a polystyrene sensible heat recovery unit.